Isokinetic profile of shoulder muscle strength at terminal ranges of a functional movement pattern in elite junior female volleyball players - Sekir, U.; Akova, B.; Punduk, Z.; Gur, H.; Kucukoglu, S. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Isokinetic muscle strength testing is used by clinicians for the analyses of strength and strength differences of the shoulder muscles, for the assessment of concentric and eccentric peak torque, or for detecting muscle strength loss after injuries in overhead athletes (Alfredson, 1998; Wang, 2000). Because multifarious test positions were claimed as best strength measures for shoulder muscles, numerous test positions and speeds of testing have been reported (Chandler, 1992). The antagonist / agonist ratios for peak torque have been studied in several studies for shoulder external rotation / internal rotation (Ng, 2002; Noffal, 2003). The ER/IR ratios are used as guidelines for managing strength training or injury rehabilitation by assessing changes in the ratio after training or injury. While these ratios have been helpful in providing insight into the evaluation of patient strength, they may fall short of reflecting muscle function during activity. The purpose of this study was to measure shoulder isokinetic muscle strength during and at terminal ranges of a functional movement pattern and to develop a bilateral descriptive profile in elite junior female volleyball players. Methods Twelve elite junior female volleyball players were tested on both shoulders in the flexion/abduction/external rotation (F/AB/ER) and extension/adduction/internal rotation (E/AD/IR) functional movement patterns at speeds of 30°/sec, 240°/sec and 400°/sec using a Cybex 6000 isokinetic system. Concentric peak torque and ratio of F/AB/ER to E/AD/IR were calculated during the entire range of movement for the three angular velocities and at the terminal ranges of extension and flexion for the angular velocity of 30°/sec. Analysis of the parameters between both shoulders was carried out using the Mann Whitney U test. Results While taken up for the entire functional range of motion there was not any significant difference in the flexor and extensor peak torque and in the ratio of F/AB/ER to E/AD/IR at three angular velocities between the dominant and non-dominant shoulders (Tab. 1, p>0.05). The terminal range ratios of extension (5º - 25º of E/AD/IR) were found to be 0.70±0.21 and 0.68±0.20 for the dominant and non-dominant shoulders, respectively and these were also not significant different (p>0.05). On the other hand, the terminal range ratios of flexion (115º - 135º of F/AB/ER) revealed a statistically significant difference with the values of 0.78±0.11 and 0.66±0.13 for the dominant and non-dominant shoulders, respectively (Tab. 2, p<0.05). Discussion/Conclusion These data show that measurement in the terminal ranges, reflecting the beginning of the service and spike in volleyball, are more valuable than the strength values obtained only during the entire range of motion of a functional movement pattern. Additionally, terminal range values provide precious information in monitoring, prevention and rehabilitation of shoulder injuries in female volleyball players.